Consonants at the juncture of verb morphemes - Kazlauskienė, Asta (Lietuvių kalba, 2012)
The boundaries of morphemes constituting words in the Lithuanian language are not always clear, various phonological processes take place at a morpheme juncture: either front or back sounds are adjusted to the adjacent sounds of the other morpheme, sometimes morphemes overlap – sounds are skipped or contracted. The reasons of such variation are phonological (when geminates that are not characteristic of the Lithuanian language are eliminated, degemination, dissimilation, contraction take place) and phonetic (when sounds are switched or omitted to make pronunciation easier, metathesis, elimination take place). The former changes are more frequent. The research data for the article have been compiled from the Reverse Dictionary of Contemporary Lithuanian and the electronic Database of Morphotactics and Phonotactics which is compiled on the basis of coherent texts. All in all, about 1,300 examples from the dictionary and about 500 language use examples are analysed in the article. Although consonant variations are briefly discussed in more than one research work of Lithuanian linguists, all the classifications proposed in them have their drawbacks. The present article discusses the principles that could be followed in classifying consonant changes that take place at morpheme juncture in the Lithuanian language.